Neural processing of emotional facial stimuli in specific phobia: An fMRI study. Issue 8 (5th July 2021) - Böhnlein, Joscha; Leehr, Elisabeth J.; Roesmann, Kati; Sappelt, Teresa; Platte, Ole; Grotegerd, Dominik; Sindermann, Lisa; Repple, Jonathan; Opel, Nils; Meinert, Susanne; Lemke, Hannah; Borgers, Tiana; et al.
Abstract: Background: Patients with specific phobia (SP) show altered brain activation when confronted with phobia‐specific stimuli. It is unclear whether this pathogenic activation pattern generalizes to other emotional stimuli. This study addresses this question by employing a well‐powered sample while implementing an established paradigm using nonspecific aversive facial stimuli. Methods: N = 111 patients with SP, spider subtype, and N = 111 healthy controls (HCs) performed a supraliminal emotional face‐matching paradigm contrasting aversive faces versus shapes in a 3‐T magnetic resonance imaging scanner. We performed region of interest (ROI) analyses for the amygdala, the insula, and the anterior cingulate cortex using univariate as well as machine‐learning‐based multivariate statistics based on this data. Additionally, we investigated functional connectivity by means of psychophysiological interaction (PPI). Results: Although the presentation of emotional faces showed significant activation in all three ROIs across both groups, no group differences emerged in all ROIs. Across both groups and in the HC > SP contrast, PPI analyses showed significant task‐related connectivity of brain areas typically linked to higher‐order emotion processing with the amygdala. The machine learning approach based on whole‐brain activity patterns could significantly differentiate the groups with 73% balanced accuracy. Conclusions: Patients suffering from SP are characterized by differences in the connectivity of the amygdala and areas typically linked to emotional processing in response to aversive facial stimuli (inferior parietal cortex, fusiform gyrus, middle cingulate, postcentral cortex, and insula). This might implicate a subtle difference in the processing of nonspecific emotional stimuli and warrants more research furthering our understanding of neurofunctional alteration in patients with SP.